Perempuan dan Akses terhadap Hutan Adat Kasepuhan Karang, Banten - Nur Laeliyatul Masruroh (Laboratorium Sosiologi, Program Studi Sosiologi, Fakultas Ilmu Sosial, Universitas Nahdlatul Ulama Indonesia (UNUSIA) Jakarta, 2024)
The indigenous community of Kasepuhan Karang in the Province of Banten has struggled extensively to assert sovereignty over the forest land they have traditionally managed. The Social Forestry initiative under the Customary Forest scheme established by the Ministry of Environment and Forestry (Kementerian Lingkungan Hidup dan Kehutanan) in 2016 opened avenues for intervention by various stakeholders, including the state, non-governmental organizations (NGOs), and the private sector, impacting women and their access to the forest. This research examines women's access to the customary forests of Kasepuhan Karang post-establishment of the Customary Forest. Using ethnographic methods involving direct observation and in-depth interviews with key figures in the Kasepuhan Karang indigenous community in Jagaraksa Village, Muncang District, Lebak Regency, Banten Province, from October 7-15, 2023. The study findings indicate that legal access to customary forests has influenced women's access in regarding division of labor, forms of participation, and benefit reception. The Customary Forest scheme in Kasepuhan Karang has expanded access for Indigenous communities, particularly women, to the forests and has brought about social transformations, though women's participation remains suboptimal. Women contribute to maintaining certain traditional rituals in forest resource management, both stemming from longstanding customs and external interventions. Patronage, such as village heads (Jaro), holds significant influence over access issues.